2015
DOI: 10.1002/qj.2693
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting structures between the decoupled and coupled states of the stable boundary layer

Abstract: Different aspects of the stable boundary-layer structure are contrasted between the very stable and the weakly stable regimes from a new point of view. This study finds a limit wind speed, referred to as the crossover threshold, when the average vertical gradient of the turbulent kinetic energy switches sign at all observational levels. When the wind speed exceeds this transition, the entire stable boundary layer becomes vertically fully coupled. Consequently the very stable boundary layer in this study is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 46 publications
13
92
1
Order By: Relevance
“…This threshold has been examined in a number of other recent studies (e.g. Van de Wiel et al 2012;Acevedo et al 2015). This threshold V appears to some degree in all of the datasets considered here (Fig.…”
Section: Wind-speed Dependencementioning
confidence: 71%
“…This threshold has been examined in a number of other recent studies (e.g. Van de Wiel et al 2012;Acevedo et al 2015). This threshold V appears to some degree in all of the datasets considered here (Fig.…”
Section: Wind-speed Dependencementioning
confidence: 71%
“…Several observational studies indeed show a threshold wind speed for the existence of continuous turbulence (e.g. King 1994;Sun et al 2012;Acevedo et al 2015). More recent studies provide compelling observational evidence for the division into two regimes based on MSHF theory (Hooijdonk et al 2015;Monahan et al 2015;Bonin et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Mahrt 1998;Fernando and Weil 2010;Monahan et al 2011;Sun et al 2012;Mahrt 2014;Bonin et al 2015;Acevedo et al 2015;Hooijdonk et al 2015). The weakly stable boundary layer (WSBL) generally occurs when winds are strong or when clouds are present.…”
Section: Introductionmentioning
confidence: 99%
“…The relative magnitude of those two terms from the turbulent kinetic energy budget equation ultimately leads to two distinct regimes in stable boundary layer (SBL) [6][7][8][9]. A decoupled regime is characterized by light winds and weak turbulence that can alternate with periods with more intense turbulence, in a phenomena known as global intermittency, or just intermittency [6].…”
Section: Introductionmentioning
confidence: 99%
“…During the same night, the flow can switch regimes, and those changes can occur intermittently or in an organized way and can lead to temperature variability as large as 10 K [11]. Recent studies [8][9][10] have identified that to a large extent the SBL regime is solely determined by mean wind speed. Anyhow, atmospheric models do not usually represent well 2 Advances in Meteorology the SBL variability of regimes, and it is pointed out as one of the causes of the unsuccessful prediction of the DTR behavior [12].…”
Section: Introductionmentioning
confidence: 99%